2006
DOI: 10.1118/1.2361080
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of different kilovoltage x‐ray energy for three‐dimensional converging stereotactic radiotherapy system: Monte Carlo simulations with CT data

Abstract: We are investigating three-dimensional converging stereotactic radiotherapy (3DCSRT) with suitable medium-energy x rays as treatment for small lung tumors with better dose homogeneity at the target. A computed tomography (CT) system dedicated for non-coplanar converging radiotherapy was simulated with BEAMnrc (EGS4) Monte-Carlo code for x-ray energy of 147.5, 200, 300, and 500 kilovoltage (kVp). The system was validated by comparing calculated and measured percentage of depth dose in a water phantom for the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Although we used lower energy photons and very small fields to test the ability of our microscope-film system to measure penumbra, the experimental measurement of penumbra for such fields and energies would be useful in verifying a number of recent theoretical publications. For example, Deloar et al, 41 using Monte Carlo simulations, describe a novel computed tomography stereotactic radio-therapy system capable of delivering more conformal doses to target volumes using kilovoltage x rays. Iwamoto et al 42 have reported on the treatment of canine brain tumors using kilovoltage x rays from a modified computed tomography scanner.…”
Section: Discussionmentioning
confidence: 99%
“…Although we used lower energy photons and very small fields to test the ability of our microscope-film system to measure penumbra, the experimental measurement of penumbra for such fields and energies would be useful in verifying a number of recent theoretical publications. For example, Deloar et al, 41 using Monte Carlo simulations, describe a novel computed tomography stereotactic radio-therapy system capable of delivering more conformal doses to target volumes using kilovoltage x rays. Iwamoto et al 42 have reported on the treatment of canine brain tumors using kilovoltage x rays from a modified computed tomography scanner.…”
Section: Discussionmentioning
confidence: 99%
“…(but lower than that used for current megavoltage photon therapies) is adequate for human applications (4). In addition, long irradiation time was needed in our study.…”
Section: Issues Expected In Clinical Applicationmentioning
confidence: 97%
“…One rabbit did not undergo irradiation and served as a control. The irradiation doses were regulated by changing the beam-on duration based on a dose rate of 5 Gy/min at a depth of 3-cm in water-equivalent material (4,6). For each irradiation event, the X-ray tube was continuously rotated in one direction to achieve a rotational irradiation arc of 360 .…”
Section: Experimental Irradiation Of Rabbit Lungsmentioning
confidence: 99%
“…In general, the focal spot sizes for orthovoltage units are larger than those for standard 6 MV linear accelerators; however, the geometric penumbra may be minimized through the use of collimating cones near the surface of the volume to be irradiated. Multiple studies in SBRT and SRS have shown promise for the use of orthovoltage energy photons, with both theoretical and physical orthovoltage systems showing improvements in dose gradient, conformality, and homogeneity of stereotactic plans compared to standard megavoltage energy photons . In addition, orthovoltage energies have been noted as the ideal energy range for small animal irradiations .…”
Section: Introductionmentioning
confidence: 99%